A luta do movimento feminista por direitos durante a pandemia da Covid-19 - (:unkn) unknown (UNIFAP - Universidade Federal do Amapá, 2023)
The article discusses social movements, drawing attention to the struggles of the feminist movement for women's rights based on the issue of violence against women that increased during the Covid-19 pandemic. The research objectives were twofold: the first to analyze the performance of social movements in the context of the pandemic from the perspective of the feminist movement and to describe the data on aggression and violence against women and the forms of struggles and confrontations mobilized during the first waves of the pandemic in Brazil. The research methodology was qualitative and quantitative. An exploratory study was carried out using statistical data from the “Forum Brasileiro de Segurança Pública”, the “Report on a Virus, Two Wars” and the report produced by the feminist movement called “Sempreviva Feminist Organization - SOF” on violence against women in Brazil. context of the pandemic. We did a bibliographic review on social movements, feminist movements, the fight for women's rights and the context of the pandemic.
Keywords: Feminismo; Direitos das mulheres; Pandemia; CNPQ::CIENCIAS SOCIAIS APLICADAS; ODS 5 – Igualdade de gênero; ODS 3 – Saúde e bem-estar; ODS 16 – Paz, justiça e instituições eficazes; ODS 10 – Redução das desigualdades